Teacher's Role in Applying Audio Visual Media in Science Learning - Yulanti S. Mooduto; Indri Lakoro (Journal of Education Review Provision, 2021)
The problem in this study is "Can using the Numbered Head Together learning model improve the ability to read aloud students in class III SDN 1 Bone Raya Bone Bolango Regency?" The purpose of this study was to improve the students' ability to read aloud through the Numbered Head Together learning model in class III SDN 1 Bone Raya, Bone Bolango Regency. The method used in this research is Classroom Action Research (CAR) which is carried out in 2 cycles. Data collection techniques in this study were in the form of teacher activity observation, student activity observation, interviews, tests, and documentation. Initial observations of the students' average ability in reading aloud (33%) or 5 students who completed and (67%) or 10 students who had not finished. In the implementation of the first cycle class action, only 11 students (73%). In the second cycle increased to 13 people (87%). From the results of the research and discussion carried out, the research on Students' Reading Aloud Ability through the Numbered Head Together Learning Model in Class III SDN 1 Bone Raya, Bone Bolango Regency increased.